Self-neglect among the Elderly: An Overview of the Concept, Status and Assessment Tools - Hou Yongmei (New Ideas Concerning Arts and Social Studies Vol. 2, 2025)
Background: Self-neglect among the elderly is a widespread public health issue, with its incidence rate increasing year by year, seriously affecting the physical and mental health of the elderly and hindering the realization of "healthy aging". Clarifying the basic connotation of self-neglect among the elderly and developing authoritative assessment tools are of great significance for geriatric research, medical care, and nursing work. Objective: To understand the concept, current status, and assessment tools of self-neglect among the elderly. Methods: A literature search was conducted using the keywords "the elder" or "older people" or "old people" + "self-neglect" in English or Chinese in PubMed, Web of Science, CINAHL Plus, Scopus, Embase, PsycINFO, and CNKI over the past 10 years. Results: Thirty papers were included. Previous literature indicates that the incidence rate of self-neglect among community-dwelling elderly globally ranges from 18.4% to 29.1%. Self-neglect accelerates functional aging in the elderly, increasing their prevalence of diseases, hospitalization rate, suicide rate, and mortality rate. The connotation of self-neglect among the elderly is complex and multidimensional, with strong cultural dependence, and there is no unified conceptual definition. Therefore, although assessment tools have been widely developed with many achievements, there are significant differences in the number and connotation of measurement dimensions, as well as the measurement performance of the tools, affecting the comparability and generalizability of assessment results. Conclusion: Self-neglect among the elderly has increasingly attracted the attention of the academic community. However, issues such as the definition of the concept and the scientific development and reasonable selection of assessment tools still need further exploration.